Impact of “Assessment and Accreditation” Process on Quality of Higher and Medical Education in India: A Systematic Review and Meta-analysis - Venkata Venu Gopala Raju Srijampana; Bodhi Srividya Vennam; Phanindra Dulipala; Rajesh Potti (Archives of Medicine and Health Sciences)
Introduction: India’s higher education system is evolving to meet global standards, driven by initiatives like the National Education Policy 2020. Assessment and accreditation play a pivotal role in ensuring the quality and credibility of educational institutions. In India’s vast, diverse landscape, accreditation is a mechanism that enhances institutional performance, boosts accountability, and encourages continuous improvement. Despite this, the true effect of these processes on educational quality has not been thoroughly explored. This systematic review and meta-analysis aims to assess the influence of assessment and accreditation on institutional quality in India’s higher education system. Materials and Methodology: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic review and meta-analysis were conducted using databases such as Embase, Scopus, PubMed, and Google Scholar. The search focused on studies from 2000 to 2023 that evaluated the impact of accreditation on institutional quality in India. Inclusion criteria were peer-reviewed articles and reports with empirical data on the subject. The selected studies were quantitatively synthesized, and statistical meta-analytical techniques were used to calculate overall effect sizes for various quality indicators such as faculty development, infrastructure, curriculum innovation, and research productivity. Results: From 25 studies, the meta-analysis revealed an overall effect size of 0.52 for the positive impact of accreditation on institutional quality. Significant improvements were noted in infrastructure (effect size: 0.61), faculty quality (0.47), curriculum design (0.49), student outcomes (0.54), and research productivity (0.45). Public, urban, and technical institutions experienced greater improvements compared to private and rural institutions. Conclusion: Accreditation significantly improves the quality of higher and Medical education in India, positively impacting key areas such as infrastructure, faculty quality, and student outcomes. However, disparities exist, particularly between urban and rural institutions, and between public and private institutions.